Sige antarctica Kato & Pleijel 2002, new comb. - Kato, Tetsuya; Pleijel, Fredrik (Zenodo, 2002)
Sige antarctica (Hartman, 1978) new comb. Nipponophyllu m antarcticum Hartman, 1978: 142, gure 9a–d. Material examined. Holotype (USNM-46745), Weddell Sea, Antarctic. Remarks. Examination of Hartman’s type shows that it does not belong to Notophyllum . In view of the presence of a median antenna, the absence of notoaciculae, and its prolonged supra-acicular neuropodial lobes, we conrm Pleijel’s (1991) suggestion that it belongs to Sige Malmgren, 1865. : Published as part of Kato, Tetsuya & Pleijel, Fredrik, 2002, A revision of Notophyllum Örsted, 1843 (Phyllodocidae, Polychaeta), pp. 1135-1178 in Journal of Natural History 36 (10) on page 1172, DOI: 10.1080/00222930110039954, http://zenodo.org/record/5298448 : {"references": ["HARTMAN, O., 1978, Polychaeta from the Weddell Sea Quadrant, Antarctica, Antarctic Research Series, 26, 125 - 217.", "MALMGREN, 1865, Nordiska Hafs-Annulater, Ofversigt af K. Vetenskapsakademiens forhandlingar, 21, 1 - 110."]}